Participation in research and innovation exhibitions: E-learning applications in Arabic Language - Sahrir, Muhammad Sabri (Akademi Pengajian Islam, Nilam Puri, University of Malaya (UM), 2017)
Arabic learning is in dire need for advance teaching and learning aids, especially with the integration of advanced multimedia application by using computer assisted applications, and learning courseware such as educational websites, digital or online language games, mobile learning applications, etc. In fact these applications have already been developed and explored by many researchers all over the world in various platforms such as web-based, CD-based, cloud based as well as mobile-based applications. The potential of designing and developing these applications is not limited to the benefits for teaching and learning Arabic language per se, but it is also has prospects to go into breakthrough of the innovation exhibition and competitions which are organized locally and internationally. These events are important for the researchers to generate and promote their innovative ideas to others and has the potential to transform their research into commercial products and winning the medal awards based on the evaluation criteria in the research and innovation exhibition and competition. The purpose of this paper is to discuss several research and innovation exhibition and competitions which are being organised locally and internationally and its relationship and potential with the development of multimedia applications in the field of teaching and learning Arabic language.